Alternative paths for insertion of probes into high inclination lunar orbits - de Melo, C. F.; Macau, E. E. N.; Winter, O. C. [UNESP]; Neto, E. Vielra [UNESP] (Elsevier B.V., 2007)
The dynamics of the restricted three-body Earth-Moon-particle problem predicts the existence of direct periodic orbits around the Lagrangian equilibrium point L1. From these orbits, we derive a set of trajectories that form links between the Earth and the Moon and are capable of performing transfers between terrestrial and lunar orbits, in addition to defining an escape route from the Earth-Moon system. When we consider a more complex and realistic dynamical system - the four-body Sun-Earth-Moon-particle (probe) problem - the trajectories have an expressive gain of inclination when they penetrate in the lunar influence sphere, thus allowing the insertion of probes into low-altitude lunar orbits with high inclinations, including polar orbits. In this study, we present these links and investigate some possibilities for performing an Earth-Moon transfer based on these trajectories. (C) 2007 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: astrodynamics; mission design; earth-moon transfer; orbital maneuvers